A trajetória de uma imigrante: Anna Maria Pauletti Rech (1876-1916) e a atuação feminina nas colônias italianas do Rio Grande do Sul - Bortolanza, Karina (Universidade do Vale do Rio dos Sinos, 2023)
A widowed Italian peasant, 47 years old, mother of seven with no future in Italy, emigrates to an uncertain destination in Brazil. On Brazilian soil, she raises her children, starts her own business (a inn for muleteers in Caxias do Sul), and puts her health-related knowledge into practice, becoming a midwife. The research aims to understand the female role in the Italian immigration colonies in Rio Grande do Sul through the figure of Anna Maria Pauletti Rech, who arrived in 1876. The focus is on the places of action for women, especially widows, divorced, or single, those without a male figure as the head of the family. The methodology involves trajectory studies, emphasizing female protagonism and their relationships with the social context. By cross-referencing sources such as periodicals, baptismal books, documents from the Municipal Chamber of Caxias do Sul, and interviews, we will seek a better understanding of the character's relationships with the contemporary context. Following the case of immigrant Anna Rech will also allow us to understand the different representations created to emphasize the positive role of the female immigrant. Anna Rech had a statue erected during the celebrations of the Centennial of Italian Immigration in Rio Grande do Sul in the 1970s, aiming to exalt the figure of the immigrant woman as a mother and hardworking individual who left her place of origin to succeed in Brazilian lands. Finally, we emphasize the importance of this study in aiding the understanding of the female universe in the society formed by immigrants in Rio Grande do Sul.
Keywords: Imigração italiana; Gênero; Trajetória; Anna Rech; Italian immigration; Gender; Trajectory; ACCNPQ::Ciências Humanas::História